Creativity selected readings - Vernon, Philip Ewart 1905-1987 (Harmondsworth, Middlesex, England Penguin Education, 1970)
Of Galton's Hereditary genius / M.I. Stein, S.J. Heinze -- Psychological approaches to the biography of genius / L.M. Terman -- A psychologist examines sixty-four eminent scientists / Anne Roe -- Letter / Wolfgang Amadeus Mozart -- Letters / Peter Ilich Tchaikovsky -- Making of a poem / Stephen Spender -- Mathematical creation / H. Poincaré -- Art of thought / G. Wallas -- Adventurous thinking / F.C. Bartlett -- Creativeness of life / E.W. Sinnott -- S-R psychology and cognitive psychology / A.J. Cropley -- Creative writers and day-dreaming / S. Freud -- Towards a theory of creativity / C.R. Rogers -- Psychometric measurement of creativity / T.A. Razik -- Traits of creativity / J.P. Guilford -- Highly intelligent and the highly creative adolescent / J.W. Getzels, P.W. Jackson -- Critical notice / C.L. Burt -- Question of creativity / L. Hudson -- New look at the creativity-intelligence distinction / M.A. Wallach, N. Kogan -- Criterion problem / R.J. Shapiro -- Disposition towards originality / F. Barron -- Personality correlates of creativity: a study of American architects / D.W. MacKinnon -- Creativity and personality / R.B. Cattell, H.J. Butcher -- Prediction of creativity with the biographical inventory / C.W. Taylor, R.L. Ellison -- Education and creativity / S.J. Parnes -- Causes for concern / E.P. Torrance -- Teaching approach and divergent thinking abilities / F.A. Haddon, H. Lytton.
Summary of Galton's Hereditary genius / M.I. Stein, S.J. Heinze -- Psychological approaches to the biography of genius / L.M. Terman -- A psychologist examines sixty-four eminent scientists / Anne Roe -- Letter / Wolfgang Amadeus Mozart -- Letters / Peter Ilich Tchaikovsky -- Making of a poem / Stephen Spender -- Mathematical creation / H. Poincaré -- Art of thought / G. Wallas -- Adventurous thinking / F.C. Bartlett -- Creativeness of life / E.W. Sinnott -- S-R psychology and cognitive psychology / A.J. Cropley -- Creative writers and day-dreaming / S. Freud -- Towards a theory of creativity / C.R. Rogers -- Psychometric measurement of creativity / T.A. Razik -- Traits of creativity / J.P. Guilford -- Highly intelligent and the highly creative adolescent / J.W. Getzels, P.W. Jackson -- Critical notice / C.L. Burt -- Question of creativity / L. Hudson -- New look at the creativity-intelligence distinction / M.A. Wallach, N. Kogan -- Criterion problem / R.J. Shapiro -- Disposition towards originality / F. Barron -- Personality correlates of creativity: a study of American architects / D.W. MacKinnon -- Creativity and personality / R.B. Cattell, H.J. Butcher -- Prediction of creativity with the biographical inventory / C.W. Taylor, R.L. Ellison -- Education and creativity / S.J. Parnes -- Causes for concern / E.P. Torrance -- Teaching approach and divergent thinking abilities / F.A. Haddon, H. Lytton.
Includes bibliographical references (pages 387-390) and indexes.
Keywords: Creative ability